Correlation between hippocampal volumes and proton magnetic resonance spectroscopy of the posterior cingulate gyrus and hippocampi in Alzheimer's disease - Park,Eun Joo (2010)
Abstract Prior studies have reported hippocampal volume loss, decrease in N-Acetylaspartate (NAA) concentration and increased myo-inositol (mI) concentration in patients with Alzheimer's disease (AD). The purpose of this study was to evaluate hippocampal volumes of AD patients and their correlation with metabolic changes detected by proton spectroscopy (1H MRS) of hippocampal formations and the posterior cingulate region. Materials and Methods: 22 patients with probable AD (18 mild, 4 moderate) and 14 elderly controls without cognitive symptoms, were enrolled in the study. Hippocampal volumetric measurements, single-voxel 1H MRS of the posterior cingulate region and of hippocampal formations were obtained. The following metabolite ratios were evaluated: NAA/Cr, mI/Cr, mI/NAA. Statistical analysis was performed to detect differences and correlations between these parameters in patients and controls. Results: The hippocampal volume of patients and controls did not differ significantly. The results of 1H MRS differed significantly between patients and controls in the hippocampal formations (mI/Cr, mI/NAA) and posterior cingulate region (NAA/Cr, mI/Cr, mI/NAA). The best predictor of AD diagnosis was NAA/Cr in the posterior cingulate region, having a sensitivity of 0.899 and specificity of 0.800. There was no correlation between hippocampal volumes and the results of 1H MRS in patients with AD. Conclusions: The results of 1H MRS differed significantly between patients and controls in hippocampal formations and the posterior cingulate region, with NAA/Cr proving to be the best predictor for AD. No correlation between hippocampal volumes and the results of 1H MRS in patients with AD was observed.